Acute retinal necrosis: pathophysiological aspects, diagnosis, and treatment - Vesela Mitkova-Hristova; Nina S. Stoyanova (Folia Medica, 2022)
Acute retinal necrosis (ARN) is a devastating viral infection commonly associated with varicella zoster virus (VZV) and herpes simplex virus types 1 and 2 (HSV-1, HSV-2). Typically, ARN affects individuals without immune status disorders between the ages of 50-70. In two-thirds of the cases, one-eye involvement is observed and the inflammation can be presented as panuveitis. The most characteristic clinical manifestations are vitreitis, occlusion of the retinal arterioles, and peripheral necrotizing retinitis. Retinitis presents with the appearance of deep, multifocal, yellowish-white foci, typically localized in the peripheral retina. Systemic antivirals are the first treatment of choice for ARN. The goal of the therapy is to stop the viral replication and disease progression in the affected eye, as well as to prevent involvement of the healthy eye. The other eye can be attacked in an interval of 5 days to 30 years. The visual prognosis after illness is poor. Early diagnosis and timely initiation of treatment play an important role in maintaining visual acuity and preventing the other eye from being affected.